Foraging behaviour of sympatrically breeding macaroni (Eudyptes chrysolophus) and chinstrap (Pygoscelis antarcticus) penguins at Bouvetøya, Southern Ocean - Narvestad, Audun; Kovacs, Kit M.; Lydersen, Christian; Lowther, Andrew D. (Polar Research, 2022)
Species with similar ecological requirements that overlap in range tend to segregate their niches to minimize competition for resources. However, the niche segregation possibilities for centrally foraging predators that breed on isolated Subantarctic islands may be reduced by spatial constraints and limitations in the availability of alternative prey. In this study we examined spatial and trophic aspects of the foraging niches of two sympatrically breeding penguin species, macaroni (Eudyptes chrysolophus; MAC) and chinstrap (Pygoscelis antarcticus; CHIN) penguins, at Bouvetøya over two breeding seasons. To measure at-sea movements and diving behaviour, 90 MACs and 49 CHINs were equipped with GPS loggers and dive recorders during two austral summer breeding seasons (2014/15 and 2017/18). In addition, blood samples from tracked birds were analysed for stable isotopes to obtain dietary information. CHINs displayed marked interannual variation in foraging behaviour, diving deeper, utilizing a larger foraging area and displaying enriched values of δ15N in 2014/15 compared to the 2017/18 breeding season. In contrast, MACs dove to similar depths and showed similar δ15N values, while consistently utilizing larger foraging areas compared to CHINs. We suggest that low krill abundances in the waters around Bouvetøya during the 2014/15 season resulted in CHINs shifting toward a diet that increased their niche overlap with MACs. Our findings may partly explain the decreasing number of breeding CHINs at the world’s most remote island, Bouvetøya, while also highlighting the importance of characterizing niche overlap of species using multi-season data sets.
Keywords: Bouvetøya; NARE ekspedisjoner; biotelemetri; marin biologi; pingviner

Pathogen surveillance in Southern Ocean pinnipeds - Núñez-Egido, Sandra; Lowther, Andrew; Nymo, Ingebjørg H.; Klein, Jörn; Breines, Eva M.; Tryland, Morten (Polar Research, 2020)
Knowledge of the health status and potential effect of disease outbreaks among Southern Ocean fauna may be decisive for its conservation. We assessed the exposure and infection of Antarctic fur seals (Arctocephalus gazella, AFS) and Southern elephant seals (Mirounga leonine, SES) to parapoxvirus, Phocid alphaherpesvirus-1 (PhHV-1), smooth Brucella spp. and Toxoplasma gondii. AFS (n = 65) serum and swab samples, and SES (n = 13) serum samples from the sub–Antarctic island of Bouvetøya (54°25’S, 03°22’E) were collected during two austral summers (2014/15, 2017/18). Three polymerase chain reaction (PCR) tests amplifying the DNA polymerase, B2L and GIF parapoxvirus genomic regions were performed, investigating DNA from mucosal swab samples. The glycoprotein B gene was targeted to detect PhHV-1 viral DNA. Sera were assayed for T. gondii and smooth Brucella spp. antibodies with indirect enzyme-linked immunosorbent assays. Parapoxvirus PCR amplicons of the expected size were generated in two of the 29 AFS pups (nasal swabs, 2014/15), targeting the B2L (n = 2) and DNA polymerase (n = 1) genes, whereas the GIF PCR did not amplify target sequences. The PCR amplicons were sequenced and blasted in GenBank, revealing highest similarity with a seal parapoxvirus, confirming the presence of the virus in AFS for the first time. No PhHV-1 amplicons were generated, and antibodies against T. gondii or smooth Brucella spp. were not detected. Our data indicate that these seals are host for parapoxvirus but are neither exposed to smooth Brucella spp. nor T. gondii. Evidence of PhHV-1 shedding was not detected.
Keywords: Bouvetøya; Sørishavet; epidemiologi; fylogenetikk; infeksjon; marin biologi; marin zoologi; pelsseler; pinnipedier; serologi; sjøelefanter; virologi

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Chinstrap penguin population genetic structure: one or more populations along the Southern Ocean? - Mura-Jornet, Isidora; Pimentel, Carolina; Dantas, Gisele P M; Petry, Maria Virginia; González-Acuña, Daniel; Barbosa, Andrés; Lowther, Andrew D; Kovacs, Kit M; Poulin, Elie; Vianna, Juliana A (BMC Evolutionary Biology, 2018)
Keywords: Bouvetøya; Sørishavet; fugler; genetikk; marin biologi; ornitologi; pingviner

The seasonal evolution of shelf water masses around Bouvetøya, a sub-Antarctic island in the mid-Atlantic sector of the Southern Ocean, determined from an instrumented southern elephant seal - Lowther, Andrew D.; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
Our study makes use of a fortuitous oceanographic data set collected around the remote sub-Antarctic island of Bouvetøya by a conductivity–temperature–depth recorder (CTD) integrated with a satellite-relayed data logger deployed on an adult female southern elephant seal (Mirounga leonina) to describe the seasonal evolution of the western shelf waters. The instrumented seal remained in waters over the shelf for 259 days, collecting an average of 2.6 (±0.06) CTD profiles per day, providing hydrographic data encompassing the late austral summer and the entire winter. These data document the thermal stratification of the upper water layer due to summer surface heating of the previous year's Antarctic Surface Water, giving way to a cold subsurface layer at about 100 m as the austral winter progressed, with a concomitant increase in salinity of the upper layer. Upper Circumpolar Deep Water was detected at a depth of approximately 200 m along the western shelf of Bouvetøya throughout the year. These oceanographic data represent the only seasonal time series for this region and the second such animal–instrument oceanographic time series in the sub-Antarctic domain of the Southern Ocean.
Publisher: Routledge
Keywords: AABW; Bouvetøya; biotelemetri; hydrografi; marin biologi; oseanografi; seler

Chinstrap and macaroni penguin diet and demography at Nyrøysa, Bouvetøya - Niemandt, Corne; Kovacs, Kit M; Lydersen, Christian; Dyer, Bruce M; Isaksen, Kjell; Hofmeyr, G J Greg; Mehlum, Fridtjof; de Bruyn, P J Nico (Antarctic Science, 2016)
Publisher: Cambridge University Press
Keywords: Bouvetøya; klimaendringer; krill; pelsseler; pingviner; plankton

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Publisher: Routledge
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

Post-breeding at-sea movements of three central-place foragers in relation to submesoscale fronts in the Southern Ocean around Bouvetøya - Lowther, Andrew D; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg J G; Kovacs, Kit M (Antarctic Science, 2014)
Publisher: Cambridge University Press
Keywords: Bouvetøya; oseanografi; pelsseler; pingviner; satellitt; telemetri

Norske krav i Sørishavet - Utfordringer for Sjøforsvaret - Aase, Johnny Grøneng (Norsk Tidsskrift for Sjøvesen, 2013)
Norge gjorde i 2009 krav på økonomiske soner utenfor Bouvetøya og Dronning Maud Land. Slike krav fører i følge Lov om økonomiske soner med seg forpliktelser som over tid får konsekvenser for Sjøforsvaret. l den økonomiske sonen som ble erklært utenfor fastlands-Norge på 1970-tallet har det vært Kystvakten som har opprettholdt juridiksjon, overvåket miljøet og kontrollert fisket. Norske og utenlandsk fartøyer har alt begynt å fiske i norsk økonomisk sone utenfor Bouvetøya. Det foregår i dag en rivende utvikling av teknologi for gruvedrift på store havdyp. Statlige og kommersielle private aktører posisjonerer seg aktivt for å kunne utnytte naturressursene i Sørishavet. Denne forfatteren mener at det vil tvinge seg fram et behov for stedlig overvåkning, kontroll og miljøvern i de norske økonomiske sonene i Antarktis. Det eksisterer ingen robust søk- og redningstjeneste i Antarktis. Siden Norge har gjort territorielle krav har vi også en moralsk forpliktelse om å kunne komme skipbrudne og syke til unnsetning i disse områdene. Overvåkning og hevding av juridiksjon i slike store og fjerntliggende havområder vil bli komplisert og dyrt. Kystvakten har i dag verken fartøyer eller personell for å kunne utføre dette. Rundt 2020 vil de store kystvaktskipene Nordkapp, Senja og Andenes være rundt 40 år og nærme seg tidspunktet for utfasing. Klimaendringene fører til migrasjon av fisk nordover mot kaldere vann i Barentshavet, og det vil derfor bli behov for fiskeriinspeksjoner lenger nord enn i dag. Kystvakten trenger å anskaffe store erstatningsfartøy for Nordkapp-klassen, og ved prosjekteringen bør man ta høyde for at Norge også vil ha behov for en kystvaktkapasitet i Antarktis. For å redusere risikoen for over- eller feilinvesteringer vil jeg gjennomgå hvordan en allerede i dag kan benytte satellitter for å kartlegge skipstrafikken i de norske områdene i sør. Ut fra dette bakgrunnsmaterialet kan Forsvaret anslå hvor mange fartøyer som vil være nødvendig å ha i sør.
Publisher: Sjømilitære samfund
Keywords: Bouvetøya; Dronning Maud Land; Sørishavet; havrett; jus; miljøovervåking; miljøvern; naturressurser; økonomi

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Da Norge annekterte Bouvetøya - Skagestad, Odd Gunnar (Historie (Bergen), 2013)
Keywords: Bouvetøya; historie; politikk

Hvordan Bouvetøya ble norsk - Skagestad, Odd Gunnar (UD-posten: husorgan for utenrikstjenesten, 2013)
Keywords: Bouvetøya; historie; politikk

Antarctic krill swarm characteristics in the Southeast Atlantic sector of the Southern Ocean - Krafft, Bjørn A.; Skaret, Georg; Knutsen, Tor; Melle, Webjørn; Klevjer, Thor; Søiland, Henrik (Marine ecology. Progress series, 2012)
Knowledge about swarm dynamics and underlying causes is essential to understand the ecology and distribution of Antarctic krill . We collected acoustic data and key environmental data continuously across extensive gradients in the little-studied Southeast Atlantic sector of the Southern Ocean. A total of 4791 krill swarms with swarm descriptors including swarm height and length, packing density, swimming depth and inter-swarm distance were extracted. Through multivariate statistics, swarms were categorized into 4 groups. Group 2 swarms were largest (median length 108 m and thickness 18 m), whereas swarms in both Groups 1 and 4 were on average small, but differed markedly in depth distribution (median: 52 m for Group 1 vs. 133 m for Group 4). There was a strong spatial autocorrelation in the occurrence of swarms, and an autologistic regression model found no prediction of swarm occurrence from environmental variables for any of the Groups 1, 2 or 4. Probability of occurrence of Group 3 swarms, however, increased with increasing depth and temperature. Group 3 was the most distinctive swarm group with an order of magnitude higher packing density (median: 226 ind. m ) than swarms from any of the other groups and about twice the distance to nearest neighbor swarm (median: 493 m). The majority of the krill were present in Group 3 swarms, and the absence of association with hydrographic or topographic concentrating mechanisms strongly suggests that these swarms aggregate through their own locomotion, possibly associated with migration.
Publisher: Inter-Research
Keywords: Bouvetøya; Sørishavet; datainnsamling; ekkolodd; krill; marin biologi; plankton; økologi

Long-range migration of a chinstrap penguin from Bouvetøya to Montagu Island, South Sandwich Islands - Biuw, Martin; Lydersen, Christian; Nico de Bruyn, P. J.; Arriola, Aline; Hofmeyr, Greg G. J.; Kritzinger, Petrus; Kovacs, Kit M. (Antarctic Science, 2010)
We describe a long-range migration of a pre-moulting adult chinstrap penguin from Bouvetøya, a small relatively recently established colony, to the South Sandwich Islands, where large, established colonies of this species reside. The trip lasted around three weeks, covered ∼3600 km, and the time of arrival was consistent with the annual moult. The bird did not travel along the shortest path or along a constant bearing, but instead followed what appeared to be a series of two or three rhumb lines of constant bearing. Small southward and northward deviations from the general path were consistent with local water currents. Travel speeds were high during daylight but decreased at night, suggesting that resting or opportunistic feeding occurred preferentially at night. While long-range winter migrations of chinstraps to feeding areas in the vicinity of distant colonies have been previously described, this is the first observation of such a trip during the period between breeding and moulting, and the first record of an individual actually arriving at one of these distant colonies. This has implications for understanding population structure and management of this important Southern Ocean predator.
Publisher: Cambridge University Press
Keywords: Bouvetøya; NARE 2007/08; Sør-Sandwichøyene; marin biologi; pingviner; sjøfugler

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Intraspecific differences in the diet of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Bester, Marthán; Kirkman, Stephen; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2010)
Intraspecific differences in the diets of many species of pinnipeds are to be expected in view of the great differences in morphology, life history and foraging behaviour between the sexes of many species. We examined the diet of the Antarctic fur seal population at Bouvetoya, Southern Ocean, to assess intersexual differences. This was made possible by the analysis of prey remains extracted from scats and regurgitations collected in areas used primarily by one or the other sex. The results indicate that both males and females feed primarily on Antarctic krill Euphausia superba with several species of fish and squid being taken, likely opportunistically given their prevalence. Significant differences were identified in the frequency of occurrence of otoliths in scats and the percentage numerical abundance of the major fish prey species in the diet. Adult males ate a smaller quantity of fish overall, but ate significantly more of the larger fish species. The greater diving capabilities of males and the fact that they are not limited in the extent of their foraging area by having to return regularly to feed dependant offspring may play a role in the differences found between the diets of males and females. Additionally, females might be more selective, favouring myctophids because they are richer in energy than krill. The absence of major differences in the diet between the sexes at this location is likely due to the high overall abundance of prey at Bouvetoya.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; sjøpattedyr

Distribution and demography of Antarctic krill in the Southeast Atlantic sector of the Southern Ocean during the austral summer 2008 - Krafft, Bjørn A.; Melle, W.; Knutsen, T.; Bagøien, E.; Broms, C.; Ellertsen, B.; Siegel, V. (Polar Biology, 2010)
This study documents horizontal distribution and demography of Antarctic krill (Euphausia superba) from the Southern Ocean during January–March 2008. The cruise predominantly occurred in CCAMLR Subarea 48.6, where knowledge about the ecosystem is limited. E. superba were not found north of 52°S. The biomass, estimated from trawl catches, was highest (63.09 g/m2) at a station 680 km southeast of Bouvetøya and at two stations 1,400 and 600 km southeast and southwest of Bouvetøya, 54.67 and 61.38 g/m2, respectively. Body length ranged from 19 to 61 mm (N = 8,538), with a mean of 42.0 ± 6.4 mm (SD). The overall sex ratio was 1:1, 46.2% males (13.2% adults and 33.0% subadults), 46.1% females (33.6% adults and 12.5% subadults), while 7.5% were juveniles. Trawl stations dominated by adults were found west and north of Bouvetøya. Stations with high proportions of subadults and juveniles were mainly found southeast of the island. Four cluster groups were differentiated: analyzing data on krill sex proportions, maturity stages, hydrography, nutrients and chlorophyll concentrations. Two groups represented stations located in the northern part of the study area, where E. superba were absent; water temperatures were higher and the nutrient concentrations lower compared to the groups where E. superba were present. This study shows that bathymetric features like the North Weddell Ridge including Bouvetøya are important for concentrating krill probably due to water mass characteristics and advective processes which influence regional krill demography. The southern regions of CCAMLR sector 48.6 are essential for understanding regional krill recruitment and production.
Keywords: Bouvetøya; Sørishavet; krill; marin biologi; marine økosystemer; zooplankton

The acoustic properties of Salpa thompsoni - Wiebe, Peter H.; Chu, Dezhang; Kaartvedt, Stein; Hundt, Anna; Melle, Webjorn; Ona, Egil; Batta-Lona, Paola (ICES Journal of Marine Science, 2010)
Wiebe, P. H., Chu, D., Kaartvedt, S., Hundt, A., Melle, W., Ona, E., and Batta-Lona, P. 2010. The acoustic properties of Salpa thompsoni. – ICES Journal of Marine Science, 67: 583–593.Aggregations of the salp Salpa thompsoni were encountered during the Antarctic krill and ecosystem-studies cruise on the RV “G.O. Sars” from 19 February to 27 March 2008. The salp's in situ target strength (TS), size, number of individuals in aggregate chains, and chain angle of orientation were determined. Shipboard measurements were made of Salpa thompsoni's material properties. Individual aggregates were mostly 45.5–60.6 mm in mean length; relatively rare solitaries were ∼100 mm. Chains ranged from 3 to at least 121 individuals, and in surface waters (<20 m), they showed no preferred angle of orientation. Sound-speed contrast (h) ranged from 1.0060 to 1.0201 and density contrast (g) estimates between 1.0000 and 1.0039. The in situ TS distributions peaked between −75 and −76 dB at 38 kHz, with a secondary peak at approximately −65 dB. TS ranged between −85 and −65 dB at 120 and 200 kHz and peaked around −74 dB. The measured in situ TS of salps reasonably matched the theoretical scattering-model predictions based on multi-individual chains. The backscattering from aggregate salps gives rise to TS values that can be similar to krill and other zooplankton with higher density and sound-speed contrasts.
Keywords: Bouvetøya; Sørishavet; copepoder; ekkolodd; krill; marin biologi; marine økosystemer; oseanografi; plankton

Time budgets and at-sea behaviour of lactating female Antarctic fur seals Arctocephalus gazella at Bouvetøya - Biuw, Martin; Krafft, Bjørn A.; Hofmeyr, G. J. Greg; Lydersen, Christian; Kovacs, Kit M. (Marine ecology. Progress series, 2009)
We present the first data on attendance patterns, at-sea movements and diving behaviour of Antarctic fur seals breeding at Bouvetøya (Bouvet Island), Southern Ocean. While other colonies have been extensively studied, this remote and second largest global population remains relatively unknown. Time depth recorders and satellite relay data loggers were deployed on breeding females during the 2000–2001 and 2001–2002 summers. Attendance and foraging patterns were similar to those observed at colonies in the Scotia Sea region where Antarctic krill is the predominant prey. Early to mid-lactation trips ranged within ~100 km of the island, usually towards the west. The dominant direction shifted later in the season and the range also increased markedly to a peak between early February and early March. Solar elevation influenced arrivals and departures from the island, with most departures occurring around sunset. Diurnal variations in diving behaviour were consistent with the vertical migration of krill. Diving frequency was higher at night and diving effort peaked around morning twilight. Afternoon deep diving was common, suggesting that females might target dense daytime krill aggregations between the photic zone and the thermocline. Trip durations increased throughout early to mid-lactation, peaking in late January to early March, before again decreasing towards the end of lactation. Our results illustrate the substantial variability, both between individuals and within individuals over time, that is likely to reflect variations in prey distribution and in the growth requirements of pups. Such variations need to be taken into account when estimating habitat use and resource utilisation in marine top predators.
Publisher: Inter-Research
Keywords: Bouvetøya; krill; marin biologi; pelsseler; plankton; satellittsendere; zoologi; økologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

The distribution and speciation of iron along 6°E in the Southern Ocean - Croot, Peter L.; Andersson, Karen; Öztürk, Murat; Turner, David R. (The SWEDARP 1997/98 Expedition, 2004)
The distribution and speciation of iron was determined along a transect in the eastern Atlantic sector (6°E) of the Southern Ocean during a collaborative Scandinavian/South African Antarctic cruise conducted in late austral summer (December 1997/January 1998). Elevated concentrations of dissolved iron (>0.4nM) were found at 60°S in the vicinity of the Spring Ice Edge (SIE) in tandem with a phytoplankton bloom, chiefly dominated by Phaeocystis sp. This bloom had developed rapidly after the loss of the seasonal sea ice cover. The iron that fuelled this bloom was mostly likely derived from sea ice melt. In the Winter Ice Edge (WIE), around 55°S, dissolved iron concentrations were low (<0.2nM) and corresponded to lower biological productivity, biomass. In the Antarctic Polar Front, at approximately 50°S, a vertical profile of dissolved iron showed low concentrations (<0.2nM); however, a surface survey showed higher concentrations (1–3nM), and considerable patchiness in this dynamic frontal region. The chemical speciation of iron was dominated by organic complexation throughout the study region. Organic iron-complexing ligands ([L]) ranged from 0.9 to 3.0nM Fe equivalents, with complex stability logKFeL′=21.4–23.5. Estimated concentrations of inorganic iron (Fe′) ranged from 0.03 to 0.79pM, with the highest values found in the Phaeocystis bloom in the SIE. A vertical profile of iron-complexing ligands in the WIE showed a maximum consistent with a biological source for ligand production and near surface minimum possibly consistent with loss via photodecomposition. This work further confirms the role iron that has in the Southern Ocean in limiting primary productivity.
Keywords: Bouvetøya; Sørishavet; biogeokjemi; marin kjemi; oseanografi

Counts of southern elephant seals, Mirounga leonina, at Bouvet Island - Kirkman, S. P.; Hofmeyr, G. J. G.; Bester, M. N.; Isaksen, K. (Polar Biology, 2001)
Southern elephant seals were counted and classified into subjective sex-age classes on a weekly basis during expeditions to Bouvet Island in the austral summers of 1996/1997 and 1998/1999. The expeditions coincided with the moulting period of elephant seals aged one year and older. The presence of weaned pups at the principal haulout site, Nyrøysa/Westwindstranda, during the latter expedition, indicates that breeding took place here during 1998. Elephant seal counts from previous expeditions are summarised.
Keywords: Bouvetøya; NARE 1996/97; NARE 1998/99; marin biologi; pinnipedier; seler

Historien om skuta Vesleper - Olsen, Else Mehren (Follominne: årbok, 2001)
Keywords: Antarktis; Bouvetøya; Peter I. Øy; Sørishavet; ekspedisjoner; historie; hvalfangst

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Publisher: John Wiley & Sons, Ltd
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler

Prey of Antarctic fur seals at Bouvetøya, Southern Ocean - Klages, Norbert; Hofmeyr, Greg; Gjertz, Ian (Polar Record, 1999)
Publisher: Cambridge University Press
Keywords: Bouvetøya; pelsseler; pinnipedier; seler; zoologi

Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Publisher: [Routledge]
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

Den norske antarktisekspedisjonen (NARE) 1996/97 - Haugland, Jan Erling (Polarboken, 1998)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1996/97; logistikk

Bouvetøya, Subantarktiko - Næstvold, Alf (Polarboken, 1998)
Keywords: Bouvetøya; ekspedisjoner; logistikk

Miljøovervåking på Bouvetøya - Bakken, Vidar; Isaksen, Kjell; Mehlum, Fridtjof; Gjertz, Ian (Natur, 1997)
Keywords: Bouvetøya; biologi

Bouvetøya: et norsk naturreservat - Sømme, Lauritz (Fauna, 1992)
Keywords: Bouvetøya; fauna; forvaltning; natur

Distribution of selenium binding proteins in liver from two species of penguins from Bouvetøya - Norheim, Gunnar; Mehlum, Fridtjof; Bech, Claus; Moksnes, Milica T. (Polar Research, 1991)
Chinstrap penguin Pygoscelis antarctica and macaroni penguin Eudyptes chrysolophus were collected at Bouvettfya in the south Atlantic. The average hepatic selenium levels for the two species were 6.6 ± 2.9 and 23.6 ± 3.4 ng/g wet weight (P < 0.001), respectively. The total hepatic glutathione peroxidase (GSH-Px) activity in the two species was 629 ± 58 and 838 ± 88 u.kat/kg (P < 0.001), respectively. The average selenium dependent GSH-Px activity was 96 ± 3.2% of the total activity. All selenium was present in the cytosol. The selenium binding compounds were separated on Sephadex G-75 into three fractions, a high molecular weight fraction, a metallothionein fraction, and a third non-protein selenium containing fraction. There seems to be an agreement between the amount of selenium recovered in the first fraction and the GSH-Px activity. In chinstrap and macaroni penguins, the percentage of hepatic selenium recovered in the third non-protein fraction was 83 ± 2.6 and 94 ± 1.1% (P < 0.001), respectively.
Keywords: Bouvetøya; NARE 1984/85; farmakologi; miljøgifter; pingviner; zoologi

Bibliographia Phytosociologica. Norwegian possessions in the polar regions - Sunding, Per (Excerpta botanica, Sectio B, 1990)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; bibliografi; botanikk; polarområdene

Frimerkespalten - Tandberg, Arne Ingar (Skipet, 1990)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; filateli; historie; logistikk; skip

Botany of Bouvetøya, South Atlantic Ocean. II. The terrestrial vegetation of Bouvetøya - Engelskjøn, Torstein (Polar Research, 1987)
Keywords: Bouvetøya; botanikk; forskning; planter

Levels and interactions of heavy metals in sea birds from Svalbard and the Antarctic - Norheim, Gunnar (Environmental Pollution (Barking, Essex: 1987), 1987)
Samples of liver and kidney from 92 seabirds of ten species collected on Spitsbergen and in the Antarctic, were analysed for their content of copper, zinc, cadmium, lead, mercury and selenium. Significantly higher levels of copper and zinc were observed in birds from Spitsbergen than in those from the Antarctic, while the opposite was true for selenium. The highest cadmium levels were found in fulmar Fulmarus glacialis and macaroni penguin Eudyptes chrysolophus. A possibility of kidney damage due to cadmium exists. The highest mercury levels were recorded in brown skua Catharacta lonnbergi collected at Bouvetøya. Lead was not detected in any of the birds. Significant correlations were observed between levels of several of the metals studied, especially between cadminum and zinc and between mercury and selenium. However, for all birds, the highest correlation coefficients were observed when the molar concentrations of cadmium plus mercury, and selenium plus zinc, were used in the calculations. Thus several protective mechanisms may operate to diminish effects of heavy metal contaminants.
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; NARE 1978/79; forurensning; fugler; miljøgifter; ornitologi

A quantitative analysis of the behaviour of the Chinstrap penguin Pygoscelis antarctica and Macaroni penguin Eudyptes chrysolophus on Bouvetoya during the late incubation and early nestling periods - Haftorn, Svein (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; pingviner; zoologi

Fugler i de norske deler av Antarktis - Mehlum, Fridtjof (Vår fuglefauna, 1986)
Publisher: Norsk ornitologisk forening
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; Peter I. Øy; ekspedisjoner; forskning; fugler; ornitologi; zoologi

Hydrolysis of proteins by peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. The hydrolysis of casein by peptide hydrolases of Antarctic krill, E. superba, has been 2. The peptide hydrolases studied included trypsin-like enzymes, carboxypeptidase A-type of enzymes, carboxypeptidase B-type of enzymes, and an aminopeptidase isolated from Antarctic krill. 3. The trypsin-like enzymes seemed to play a decisive role in the degradation of casein, whereas the carboxypeptidase A, carboxypeptidase B and the aminopeptidase had limited effect when acting on casein alone. When combined with the trypsin-like enzymes, the exopeptidases effected enhanced release of amino acids from the protein. 4. Based on the pattern of amino acids relased from casein by a crude extract of krill, and by the isolated peptide hydrolases either alone or in combination, it is concluded that the purified peptide hydrolases examined comprise the major enzymes responsible for the autoproteolytic activity of krill at neutral- to weakly alkaline pH.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

On the purification and characterization of exopeptidases from Antarctic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1986)
1. Two carboxypeptidase-A type of enzymes and two carboxypeptidase-B type of enzymes effecting hydrolysis of Hipp-l-Phe and Hipp-l-Arg respectively, have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. In addition an aminopeptidase has been partly purified. 2. The carboxypeptidases had mol. wts of 27,000 (carboxypeptidase A) and 31,000 (carboxypeptidase B). 3. Carboxypeptidase A exhibited a broad pH optimum with a maximum at pH 5.5–6.5, whereas carboxypeptidase B had a more narrow pH-optimum with a maximum at pH 7. The aminopeptidase had an optimum at about pH 8.7. 4. The carboxypeptidases were inhibited by the chelating agent 1,10-phenanthroline.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Terrestrial arthropods of Bouvetøya - Sømme, Lauritz (Polar Research, 1986)
Keywords: Bouvetøya; ekspedisjoner; forskning; midder; miter; virvelløse dyr

Suksess i syd: utvidet forskning i Antarktis (Forsvarets forum, 1985)
Keywords: Antarktis; Bouvetøya; Sørishavet; ekspedisjoner; forskning; logistikk

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The Southern giant petrel Macronectes giganteus (Gmelin) on Bouvet Island - Haftorn, Svein; Voisin, Jean-Francois (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1982)
Keywords: Bouvetøya; forskning; fugler; ornitologi; zoologi

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Mercury and persistent chlorinated hydrocarbons in antarctic birds from bouvetøya and dronning maud land - Norheim, Gunnar; Sømme, Lauritz; Holt, Gunnar (Environmental Pollution Series A, Ecological and Biological, 1982)
The concentrations of DDE, PCB, hexachlorobenzene (HCB) and mercury were determined in samples from chinstrap penguin Pygoscelis antarctica, macaroni penguin Eudyptes chrysolophus, snow petrel Pagodroma nivea, Cape pigeon Daption capense, southern fulmar Fulmarus glacialoides, south polar skua Catharacta maccormicki and brown skua Catharacta lonnbergi. The birds were taken in central parts of Vestjella in Dronning Maud Land in February 1977 and at Bouvetøya in the South Atlantic in February 1977 and January 1979. Low levels of DDE, PCB and HCB were found in the two species of penguins, snow petrel, Cape pigeon and southern fulmar, while significantly higher levels were found in south polar and brown skua. The lowest mercury levels were found in the two penguin species and snow petrel. Cape pigeon, southern fulmar and south polar skua form an intermediate group, while the highest mercury levels were found in brown skua. It is assumed that there is a connection between the present findings and the migration pattern of the different birds. The results seem to be in agreement with previous investigations.
Keywords: Bouvetøya; Dronning Maud Land; forurensning; fugler; miljøgifter; ornitologi; økologi

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

Krill off Bouvetøya and in the southern Weddell Sea with a description of larval stages of Euphausia crystallorophias - Fevolden, Svein Erik (Sarsia, 1980)
In the austral summer 1978/79 samples of krill were taken off Bouvetøya and in the southern Weddell Sea. Off Bouvetøya Euphausia superba Dana was the dominant species, but the population pattern indicates that the individuals found there were expatriates from other areas. For the first time larvae of E. superba were found in significant amounts in the southern Weddell Sea. Except from shallow water and the most southern position, they were equal in abundance to the larvae of E. crystallorophias Holt & Tattersall. Larval stages of the latter are described as is the successive spawning that takes place among the three species of krill found in the southern Weddell Sea.
Publisher: Taylor & Francis
Keywords: Bouvetøya; NARE 1978/79; Weddellhavet; dyreplankton; krill; plankton; zooplankton

Fra et opphold på Bouvetøya i 1979 - Vinje, Torgny E (Polarboken, 1980)
Keywords: Bouvetøya; ekspedisjoner; zoologi

Investigations on krill (Euphausiacea) sampled during the Norwegian Antarctic Research Expedition 1976–1977 - Fevolden, Svein Erik (Sarsia, 1979)
Krill was sampled in the Weddell Sea, farther south than ever before, and off Bouvet-öya. Five species were found: Euphausia superba, E. crystallorophias, E. frigida, E. triacantha, and Thysanoessa macrura. E. superba and E. crystallorophias were the most abundant species north and south of 74° S respectively. Length frequency analyses suggest that E. superba from the inner Weddell Sea takes three years to reach maturity. This population differed in several aspects from the populations farther north. E. crystallorophias and T. macrura were registered south to 77°45′ S, the southernmost localisation investigated. The material gives no clear evidence whether these species take one or two years to reach maturity. Their spawning activity seems to start earlier in the season than for E. superba. E. frigida and E. triacantha were only-found off Bouvetöya. Continuous echosounder recordings revealed that the total abundance of krill in the southern parts of the Weddell Sea was low, as was also the abundance on the route between the South Orkney Islands and Dronning Maud Land.
Publisher: Taylor & Francis
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; Sør-Orknøyene; Sørishavet; Weddellhavet; dyreplankton; krill; plankton; zooplankton

De norske Antarktis-ekspedisjonene 1976-77 og 1978-79: biologiske undersøkelser på Bouvetøya og i havet - Sømme, Lauritz; Fevolden, Svein Erik (Det norske videnskaps-akademi. Årbok, 1979)
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biologi; geografi

Norsk polarpolitikk ut av tåkeheimen - Leistad, Geirr I (Farmand, 1978)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene; polarpolitikk

Bouvet norsk i 50 år den 1. desember 1977 - Mosby, Håkon (Polarboken, 1978)
Keywords: Bouvetøya; historie

Cold-Hardiness of Cryptopygus antarcticus (Collembola) from Bouvetøya - Sømme, Lauritz (Oikos, 1978)
Cryptopygus antarcticus Willem were extracted from samples of mosses collected at Bouvetøya during the Norwegian Antarctic Expedition in February 1977. The body length of the collembolans from these samples ranged from 225 to 1125 μm. The collembolans had average supercooling points between -24° and -26°C. Acclimation at -5°, 0° and 12°C for various time intervals had no significant effect on their ability to supercool. Glycerol was not found in specimens acclimated at -5° and 0°C. All specimens were killed by freezing at temperatures in the range of their supercooling points. Chill-coma temperatures of the collembolans were between -2° and -7°C.
Keywords: Bouvetøya; NARE 1976/77; kuldetoleranse; leddyr; virvelløse dyr; zoologi

Meteorologiske observasjoner på antarktisekspedisjonen 1978/79 - Vinje, Torgny E. (Været: populærvitenskapelig tidsskrift, 1978)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; meteorologi

Antarktisekspedisjonen 1976/77 - Hjelle, Audun; Snuggerud, John (Amatørradio, 1977)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1976/77; ekspedisjoner

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi

Back to the Antarctic - Orheim, Olav (Research in Norway, 1977)
Publisher: Universitetsforl. Place: Oslo
Keywords: Bouvetøya; forskning; marinbiologi

Med "Polarsirkel" til Antarktis! - Orheim, Olav (Rieco-nytt, 1977)
Keywords: Antarktis; Bouvetøya; ekspedisjoner; reisebeskrivelser

Landstigning på Bouvetøya - Sømme, Lauritz (A-Magasinet, 1977)
Keywords: Bouvetøya; biologi; ekspedisjoner; meteorologi

Norsk automatisk værstasjon på Bouvetøya - Vinje, Torgny (Været: populærvitenskapelig tidsskrift, 1977)
Keywords: Bouvetøya; meteorologi; teknologi

Bouvetøya proclaimed a nature reserve (Polar Record, 1972)
Publisher: Cambridge University Press
Keywords: Bouvetøya; lovgivning

Svalbard, Jan Mayen, antarktische Besitzungen - Gjelsvik, Tore (1969)
Publisher: Utenriksdepartementet Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; polarområdene

Bouvetøya fredet som naturreservat - Norderhaug, Magnar (Norsk natur, 1965)
Publisher: Forbundet Place: Oslo
Keywords: Bouvetøya; miljøvern; naturvern

Meteorologisk problem på Bouvetøya: det verste sted på jordkloden å tilbringe et år av sitt liv - Lunde, Torbjørn (Polarboken, 1964)
Keywords: Bouvetøya; ekspedisjoner; historie; natur

Fugl i norske biland. - 2. Bouvet-øya - Holgersen, Holger (Sterna, 1960)
Publisher: Museet Place: Stavanger
Keywords: Bouvetøya; fugler; ornitologi; zoologi

Political claims in the Antarctic - Brown, Robert Neal Rudmose (World Affairs, 1947)
Keywords: Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; geografi; historie; internasjonal politikk

Bouvet-Insel - Engelmann, Gerhard (Geographische Zeitschrift, 1940)
Publisher: Franz Steiner Verlag
Keywords: Bouvetøya; geografi; historie

The Norwegian Claim in the Atlantic Sector of the Antarctic (Polar Record, 1939)
Publisher: Cambridge University Press
Keywords: Bouvetøya; internasjonal politikk; rett

The Norwegian sector of the Antarctic (The Geographical Journal, 1939)
Keywords: Bouvetøya; internasjonal politikk; rett

The Antarctic (The Geographical Journal, 1930)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Bouvetøya; Christen Christensen; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; Peter I. Øy; kartlegging; oppdagelsesreiser

Antarctic discoveries - Brown, R N Rudmose (Scottish Geographical Magazine, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Norvegia ekspedisjonene; Sørishavet; kartlegging; oppdagelsesreiser

Bouvet-Øen (The Island of Fog) - Petersen, Wilhelm (Naturens Verden, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; geologi; oppdagelsesreiser

Den Tredje »Norvegia«-Ekspedisjon 1929—1930 - Riiser-Larsen, Hjalmar (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1930)
Publisher: Routledge
Keywords: Bouvetøya; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; geografi; kartlegging

Litt om "Norveiga"-ekspedisjonen 1927-28 og dens arbeide - Holtedahl, Olaf (Norsk hvalfangst-tidende, 1929)
Keywords: Bouvetøya; Sørishavet; ekspedisjoner; forskning; geografi; marinbiologi; oseanografi

Anneksjonen av Bouvetøya i folkerettslig belysning - Ræstad, Arnold (Tidsskrift for retsvidenskap, 1929)
Keywords: Bouvetøya; jus

Die norwegische Bouvetinsel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Publisher: Perthes Place: Gotha
Keywords: Bouvetøya; Norvegia ekspedisjoner; geografi; oppdagelsesreiser

Bouvet-øen og "Norvegia"-ekspedisjonen 1927-1928 - Mosby, Håkon (Naturen, 1928)
Place: Bergen
Keywords: Bouvetøya; Norvegia ekspedisjonen; meteorologi; oppdagelsesreiser

Bouvet-øya : det omstridte antarktiske land - Nordgaard, Ole (Nidaros, 1928)
Keywords: Bouvetøya; ekspedisjoner; oppdagelsesreiser

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi

L'île Bouvet : nouvelle expédition Norvégienne dans l'Antarctique - Rabot, Charles (La Nature, 1928)
Keywords: Bouvetøya; Lars Christensen; Norvegia ekspedisjonen

Souveränitätsverhältnisse der Polargebiete : III. die südpolaren Gebiete - Smedal, Gustav ([Nordländer])
Keywords: Antarktis; Bouvetøya; Peter I. Øy; internasjonal; polarområdene; politikk